Cytotoxic Effects of Iranian Mistletoe Extract on a Panel of Cancer Cells: Cytotoxicity of Mistletoe - Sadeghi-Aliabadi, Hojjat; Ghasemi, Nasrollah; Fatahi, Ali (Iranian Journal of Pharmaceutical Sciences, 2006)
Extracts derived from Viscum album have been shown to kill cancer cells in vitro. Some studies have noted that different species of this plant collected from around the world displayed cytotoxic effects in different extents. In the present study, we evaluated the effects of Iranian mistletoe extracts on five cancer cell lines. Plants growing on hornbeam tree (Carpinus betulus) were collected, air-dried and hydroalcoholic (MeOH-H2O with 2% acetic acid) and methanolic extracts were obtained using percolation. Also the plant juice was obtained by pressing. Cytotoxicity of the extracts on a panel of cancer cells (Hela, KB, MDA-MB-468, K562 and MCF- 7) were studied using colorimetric MTT assay. Results showed that plant juice was the most cytotoxic fraction on all cancer cells tested (IC50=0.0316 mg). The IC50 of hydroalcoholic and methanolic extracts were 0.1 and 0.316 mg, respectively. These results suggest that alkaloids and huge compounds like viscotoxin and lectins extracted by press or hydroalcoholic solvents were probably responsible for their cytotoxicity. Results also indicated that Hela cells were more resistant while KB cells were more sensitive to the cytotoxic effects of the extracts. It can be concluded that cytotoxicity of Iranian mistletoe extract on the cell lines tested closely depends on the host tree and extraction methods.